400m rhythm workout - Moss, D.
The 400m event is difficult because it is run close to, but not exactly at, top speed. A good sense of pace and rhythm is therefore crucial. The following is a workout that John Smith, former coach at UCLA, recommends in his Sprints, Starts and Relays video to develop the correct sense of pace and rhythm in this demanding event. The workout consists of seven repetitions of 100m sprints, performed at race pace with 50m jog recoveries between repetitions. The interesting aspect of the workout is that the series of 100m will eventually take the athlete completely around the track, so the turns and straights are negotiated just as in an actual 400m race. The workout begins at the start of a 400m race. From this point the sprinters run 100m at race pace. For example, if you want your athletes to reach a time of 52 sec. in 400m, they should aim to cover each 100m in 13 sec. After the first 100m the athletes jog back 50m marked on the track and run the next 100m in 13 sec., finishing at the 150m mark. They then jog back 50m to the 100m mark and sprint to the 200m mark. This pattern continues until the athletes cross the finishing line on the final (seventh) repetition. There are, of course variations. Early in the season, for example, you might wish to begin with a less stressful version of this workout. In this case have your sprinters start at the 100m mark, instead of the start of the 400m. This workout will now consist of five, instead of seven repetitions. On the other hand, you can increase the difficulty of the workout for some progression. Simply speed up each 100m and/or decrease the number of repetitions but increase the length of the repetitions.